IMPLEMENTASI SMART CITY DALAM PELAYANAN PUBLIK DI KOTA AMBON - ANDRE HOSEA TAMBUNAN; PIETER SAMMY SOSELISA; AHMAD ROSANDI SAKIR (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
This study aims to analyze the implementation of Smart City policy in improving public service quality in Ambon City as an archipelagic urban area. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The research informants included officials from the Ambon City Communication and Information Office and community members as service users. Data were analyzed inductively through data reduction, data display, and conclusion drawing. The findings indicate that Smart City implementation in Ambon City has promoted digital transformation in public services, particularly within the smart governance dimension. However, its effectiveness remains limited due to constraints in human resource capacity, uneven digital infrastructure, insufficient inter-organizational coordination, and varying levels of digital literacy among citizens. Moreover, archipelagic geographical conditions and socio-cultural characteristics significantly influence the adoption of digital services. This study concludes that Smart City success depends not only on technological advancement but also on institutional capacity, implementers’ attitudes, bureaucratic structure, and the broader social, economic, and political environment. The results provide insights for developing more adaptive and sustainable Smart City policies in archipelagic regions.